PENAMBAHAN KOSAKATA DAN PENINGKATAN NILAI KEHIDUPAN PADA ANAK TUNARUNGU MELALUI MUSIKALISASI PUISI - Sinta Munika; Sri Nasriah; Luthfi Dyah; Ubaidurrosyid A (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
The student creativity program in community services is aimed at using musicalpoems as the media to improve the vocabularies of deaf children and internalizingmoral values into them. The methods are lecturing, demonstration, practice and performance.The performance of musical poems is to build children’s self confidence.The activities took four months for the program preparation, implementation andthen evaluation. The program is carried out among six students of Widya Mulia SpecialSchool, Pundong, Bantul, Yogyakarta. The use of musical poem is found to improvethe vocabularies of deaf children. It is shown in their written and spoken communication.Besides, the children are able to enact moral values such as religiousity, confidence,autonomy, discipline and honesty. Musical poems are suitable to be implementedamong deaf children based on their level of hearing ability. Therefore, theprogram successfully solves the deaf children’ problems in language learning. It isrecommended that teachers in the school implement the program for developing deafchildren’s language skills. The children are also able to share knowledge and experiencesto others for a better life.